Knowledge and Misconceptions About Diabetes Mellitus in Semarang: An In-Depth Survey Analyzing the Impact of Public Awareness on Prevention and Management - Wilson Setiawan, Andreas; Rahel Konoralma, Amanda; Anggraini, Tyas; Melki; Maya Chandra Khodijah, Ira; Ratna Wulan, Widya (International Journal of Health Literacy and Science, 2024)
Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia resulting from impaired insulin secretion, insulin action, or both. According to the IDF data, in 2021, there were 537 million people with diabetes globally, with more than 70% of them undiagnosed. In Semarang City, in 2023, there were 41,468 reported cases of diabetes, with the majority in the age group of 46-65 years. Public knowledge about diabetes, including its symptoms, risk factors, prevention, and management, is crucial to combat this disease. This research employed a descriptive-analytic epidemiological method with a Rapid Survey design. Data was collected in November 2024 at the Pramita Laboratory in South Semarang. The study population consisted of participants from a health education program themed "All We Know About Diabetes Mellitus," with a sample size of 90 respondents selected through total sampling. Data analysis was conducted using descriptive statistics. The findings revealed significant gaps in public knowledge about diabetes, including its etiology, classification, risk factors, diagnostic criteria, treatment, and complications. These knowledge deficits pose critical barriers to early diagnosis and effective management of diabetes, contributing to increased morbidity, healthcare costs, and socioeconomic burden. Addressing these gaps through targeted educational programs is imperative to reduce diabetes-related complications and improve community health outcomes. The results underscore the urgency for comprehensive public health strategies to enhance diabetes awareness and support preventative measures, particularly in regions with high prevalence rates like Semarang City.